Enhancement Fault Ride-Through Capability of DFIG By Using Resistive and Inductive SFCLs - Ali Azizpour; Mehdi Hosseini; Mahmoud Samiei Moghaddam (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The number of wind turbines connected to the grid is steadily increasing in recent years. This situation forced the revision of the electric utilities grid codes requirements, to remain connected during grid faults, i.e., to ride through the faults, especially for those with power electronic converters, such as DFIGs. In fault condition, the voltage at the Point of Common Coupling (PCC) drops immediately and The grid voltage dips imposed at the connection point of the DFIG to the grid induce large voltages in the rotor windings, resulting in high rotor current, which can damage the rotor-side converter and disconnect from grid.  In this paper, resistive and inductive superconducting fault current limiter (SFCL) is used to improve the fault ride- through (FRT) of wind turbine generation system (WTGS). The WTGS is considered as a variable-speed system, equipped with a DFIG. The analytical and simulation studies of the resistive SFCL for improving FRT capability are presented and compared with the inductive SFCL.